Constructing an index of officially recorded crime: The use of confirmatory factor analysis - Parker, Robert Nash (Journal of quantitative criminology, 1986)
Researchers using officially reported crime statistics must frequently combine rates of individual crimes into a single composite. The most popular composite is the FBI Crime Index, which is the sum of the seven “Part I” crimes; alternatives include forming separate indices for personal and property crimes and weighting the crime categories by their seriousness before summing them. In this paper we construct crime composites through the use of confirmatory factor analysis methods. The results suggest that the measurement assumptions of conventional crime indices are problematic and demonstrate how more satisfactory alternatives can be developed with confirmatory factor analysis techniques.